1996
DOI: 10.1192/bjp.169.3.384a
|View full text |Cite
|
Sign up to set email alerts
|

More cases of paroxetine withdrawal syndrome

Abstract: Sm: We wish to add five more cases of paroxetine withdrawal syndrome to those reported by other authors (Barr et a!, 1994; Pyke, 1995).All of our cases occurred in young women (aged 26-39 years), without concurrent organic illness, diagnosed with major depression. Paroxetine was started at a dose of 10 mg/day in the first week and increased to 20 mg for the rest of the treatment period (12â€"14 months). The drug was well tolerated and laboratory tests were always normal through out the period. A benzodiazepine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…Our patient developed symptoms even though she was on a low dose of nefazodone and this was tapered over 3 days. Other authors have also reported discontinuation symptoms during slow tapering as well as with low doses tapering [10–13].…”
Section: Discussionmentioning
confidence: 94%
“…Our patient developed symptoms even though she was on a low dose of nefazodone and this was tapered over 3 days. Other authors have also reported discontinuation symptoms during slow tapering as well as with low doses tapering [10–13].…”
Section: Discussionmentioning
confidence: 94%
“…Less common reactions were ‘electric-shock' sensation [9,59,61,62], visual and auditory hallucination [63], nocturnal enuresis [64], pruritus [65], and emesis [6]. In most reports, symptoms lasted until paroxetine was reintroduced or switched to other medications and/or cognitive behavioral therapy [12,13,15,59,62,66]. Only in a few cases did symptoms spontaneously remit in about 2 weeks [4,8,63,67].…”
Section: Resultsmentioning
confidence: 99%
“…However, when symptoms persist and are distressing, the reinstitution of the same AD that triggered the problem or its substitution with a long-acting SSRI such as fluoxetine [26] may only postpone and aggravate the issue [86]. There are anecdotal reports on the use of clonazepam and other benzodiazepines or mood stabilizers, which, however, need to be properly tested [15,50,59,62,72]. Another neglected area of research is concerned with the role of withdrawal symptoms in assessing switching strategies that are increasingly utilized in the treatment resistance of mood and anxiety disorders [86,91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, case reports of SSRI discontinuation reactions have described ataxia leading to falls (Einbinder, 1995), fa tigue causing difficulty walking (Haddad et al, 2001) and electricshocklike sensations impairing walking and driving (Frost & Lal, 1995). Occasionally discon tinuation symptoms lead to urgent consultations and attendance at accident and emergency departments (Pacheco et al, 1996;Haddad et al, 2001).…”
Section: Clinical Relevancementioning
confidence: 99%